Pemberdayaan Ibu-Ibu Kelompok Pkk Kelurahan Serua Indah Kecamatan Ciputat Kota Tangerang Selatan Dalam Rangka Peningkatan Kinerja Pengurus - Andri Priadi; Widia Astuti; Sutiman (Universitas Pamulang, 2024)
This service is entitled Empowering Women from the PKK Group, Serua Indah Village, iputat District, South Tangerang City in the Context of Improving the Performance of SeruaIndah Pamulang Village Management, South Tangerang.The purpose of this service is to help provide direction and counseling to employees of theCommunity Development Institution (LPM) of Serua Indah Pamulang Village, South Tangerangregarding Counseling on Human Resource Development by Strengthening OrganizationalCulture through Increasing Value. The method of implementing this service is carried out inseveral activities, namely the survey stage, namely the socialization carried out by preparing various things that will be conveyed during the service activities that will be carried out which